2016
DOI: 10.5662/wjm.v6.i1.101
|View full text |Cite
|
Sign up to set email alerts
|

Study design in evidence-based surgery: What is the role of case-control studies?

Abstract: Randomized controlled trials (RCTs) are the gold standard in terms of study design, however, in the surgical setting conducting RCTs can often be unethical or logistically impossible. Case-control studies should become the major study design used in surgical research when RCTs are unable to be conducted and definitely replacing case series which offer little insight into surgical outcomes and disease processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As an interventional study type, randomized controlled trials (RCTs) are the gold standard in terms of study design, but this was not the preference of our surgeons. It may be related to the observation of Cao et al [ 6 ] that in the surgical setting, conducting RCTs can often be unethical or logistically impossible. They suggested that case-control studies should be the primary study design used in surgical research when RCTs are not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an interventional study type, randomized controlled trials (RCTs) are the gold standard in terms of study design, but this was not the preference of our surgeons. It may be related to the observation of Cao et al [ 6 ] that in the surgical setting, conducting RCTs can often be unethical or logistically impossible. They suggested that case-control studies should be the primary study design used in surgical research when RCTs are not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that case-control studies should be the primary study design used in surgical research when RCTs are not feasible. [ 6 ] The applications from surgeons also received the greatest number of requests for correction from the EC. Nearly all clinicians, including surgeons in research hospitals, work according to the “publish or perish” principle, which contributes the additional difficulty of acting as a researcher to the work of being a treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Though surgical RCTs are considered the gold standard study design [6], they are difficult to perform, and observational studies are an important evidence base in surgical research [7]. However, surgical observational studies often fail to address sources of bias suchasthroughinadequatematchingandaresometimesatriskof beingunderpowered [8].Thesechallengeshaveimplicationsforclinicalpracticeguidelinesinsurgery,asguidelinesoftenstrugglewith having low or very low certainty evidence [9].…”
Section: Limitations Of Surg Ic Al Re S E Archmentioning
confidence: 99%